Kendali Genetik Stay Greenness dan Hasil serta Identifikasi Segregan Transgresif pada Empat Populasi F2 Sorgum - Munarti; Wirnas, Desta; Trikoesoemaningtyas; Muhamad Syukur; Sobir; Didy Sopandie, (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2022)
Stay greenness in sorghum is related to the ability to maintain green leaves and photosynthesis under stress conditions. This study aimed to obtain information on the genetic control of agronomic characters, stay greenness, and the identification of transgressive segregants of four sorghum F2 populations. The research was carried out from February to May 2020 at the experimental field of IPB University (250 m asl), Bogor, West Java. The genetic materials used were the population of Numbu x Samurai 2, Kawali x Pahat, Kawali x B69, Super 2 x PI-150-20-A with their parents. The results showed that the character of seed weight per plant was controlled by many additive genes only in the Numbu x Samurai 2 and Kawali x Pahat populations, while stay greenness in all populations was controlled by many additive genes. All observed characters had broad-sense heritability values in the medium to high category. There were 18 individuals in the Kawali x B69 and Super 2 x PI-150-20-A crosses suspected to be transgressive segregants based on the character of seed weight per plant and stay greenness. The segregants would be generated through the pedigree method.Keywords: additive, gene action, genetic variation, transgressive index